The semantic structure of the dwelling names in English, German, French, Ukrainian and Russian (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The paper focuses on the nouns with the meaning of a dwelling house in English, German, French, Ukrainian and Russian. The analysis of this lexico-semantic group is based on the componential method. Two invariant and eleven differential semes are determined in the paper. They have a mixed embodiment in different languages. The semes of a person and constructional peculiarities prevail.
Keywords: semantics; componential analysis; invariant seme; differential seme; the name of a dwelling house